Lattice dynamics of cryocrystals at high pressure: Classical Cryocrystals - Horbenko, E.E.; Troitskaya, E.P.; Chabanenko, Val.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The lattice dynamics of cryocrystals is investigated from first principles in the framework of the Tolpygo model over a wide range of pressures. The phonon frequencies in rare-gas solids are calculated in terms of models that go beyond the scope of adiabatic approximation. At high pressure the phonon spectrum along the D and ∑ directions is distorted and the longitudinal L- and transverse T2-modes soften as a result of the electron–phonon interaction, with the relative contribution decreasing in the sequence Ar, Kr, Xe. The calculated phonon frequencies are in good agreement with the experimental data for argon crystals of a pressure3.1 GPa.